2005
DOI: 10.1002/path.1840
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic spread of ductal pancreatic adenocarcinoma is independent of lymphangiogenesis

Abstract: Early lymph node metastasis is common in pancreatic ductal adenocarcinoma (PDAC). The present study has examined the relationship of lymphatic spread to lymph vessel development and the expression of lymphangiogenic cytokines in a series of well-characterized PDACs. The hot spot method revealed the intratumoural and peritumoural lymphatic vessel density (LVD) to be slightly higher in PDACs than in the normal pancreas. The average intratumoural LVD, however, was strikingly decreased. There was no overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…7,12 Some studies have shown an inverse correlation between tumor aggressiveness and intratumoral lymphatic vessel density. 4,9,10,11 These results suggest that intratumoral lymphatic vessels, especially in the tumor center, are destructed by the tumor growth and the lymphatic vessel is preserved in the tumor border in intrahepatic cholangiocarcinoma. In the current study, tumor invasion into the lymphatic vessels was frequently detected in the tumor periphery or in the peritumoral area.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…7,12 Some studies have shown an inverse correlation between tumor aggressiveness and intratumoral lymphatic vessel density. 4,9,10,11 These results suggest that intratumoral lymphatic vessels, especially in the tumor center, are destructed by the tumor growth and the lymphatic vessel is preserved in the tumor border in intrahepatic cholangiocarcinoma. In the current study, tumor invasion into the lymphatic vessels was frequently detected in the tumor periphery or in the peritumoral area.…”
Section: Discussionmentioning
confidence: 83%
“…Like our result, lymphangiogenesis do not always occur in breast cancers. 11,44 It was demonstrated that increased lymphangiogenic activity is not required for the lymphatic spread in pancreatic ductal adenocarcinoma, 7,9 and prostatic adenocarcinoma. 8,22 Several studies showed that increased lymphatic perimeters and areas were found to be correlated with presence of lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the lymphangiogenic factors VEGF-C and -D is significantly correlated with lymphangiogenesis (tumoral and nodal) and LN metastasis in a variety of primary tumors including thyroid, prostate, gastric, colorectal, lung and breast in both human and animal models [17,20,116,117]. Although VEGF-C is well-correlated with cancer metastasis, the requirement for tumor lymphangiogenesis is controversial, and there is evidence that VEGF-C can promote metastasis in the absence of tumor lymphangiogenesis [118][119][120][121][122][123]. VEGF-C can also attract macrophages [124] that can alter the tumor microenvironment to promote invasion.…”
Section: Chronic Graft Rejectionmentioning
confidence: 99%
“…Tumor invasion to regional lymph nodes is often the first sign of tumor metastasis and a marker of poor prognosis. Stimulation of growth and dilation of preexisting lymphatic vessels by the tumor facilitates tumor spread via the lymphatics (5-7) and the contribution of intratumoral lymphangiogenesis may depend on tumor type (8)(9)(10)(11)(12). Moreover, lymphangiogenic growth factors produced by the tumor may induce sinusoidal hyperplasia in the regional lymph node and this process may further contribute to tumor metastasis (13)(14)(15).…”
mentioning
confidence: 99%